A novel fusion gene PLEKHA6‐NTRK3 in langerhans cell histiocytosis. Issue 1 (26th October 2018) - Cai, Jiaoyang; Huang, Xia; Yin, Minzhi; Pan, Ci; Song, Lili; Zhan, Zhiyan; Chen, Jing; Gao, Yijin; Tang, Jingyan; Li, Yanxin; Shen, Shuhong
Abstract : Langerhans cell histiocytosis (LCH) is the most common histiocytosis with constitutive activation of the RAS–RAF–MEK–ERK (MAPKinase) cell signaling pathway. We analyzed 89 cases of BRAF and MAP2K1 mutations by Sanger sequencing, of which 18 cases showed that these two gene mutations are negative. Whole genome sequencing of suitable specimens in these negative cases revealed a translocation from the 3 intron of PLEKHA6 to the 13 intron of NTRK3 in one case. We identified that this translocation could cause a novel fusion mutation, PLEKHA6‐NTRK3. Overexpression of the PLEKHA6‐NTRK3 mutant in NIH 3T3 cells enhanced MAPKinase pathway activation, promote cell growth. Our result suggested that a new mutation need be included in LCH molecular screening panel to better define its prevalence in LCH. Abstract : What's new? Langerhans cell histiocytosis (LCH) is a rare immune and neoplastic disorder. While it is known as the most common histiocytosis with constitutive activation of the RAS‐RAF‐MEK‐ERK (MAPKinase) cell signaling pathway, its pathogenesis remains obscure. Here, whole‐genome sequencing of BRAF V600E‐negative and MAP2K1‐negative LCH cases revealed a translocation from the intron 3 of PLEKHA6 to the intron 13 of NTRK3 in one patient, identifying a novel fusion mutation. Overexpression of PLEKHA6‐NTRK3 in vitro enhanced MAPKinase pathway activation, promoting cell growth. The results support the inclusion of the fusion mutation in LCH molecular screening panel to better define its prevalence in patients.